Live birth outcome, spontaneous pregnancy and adoption up to five years after undergoing assisted reproductive technology treatment. (18th May 2017) - Volgsten, Helena; Schmidt, Lone
Summary: Introduction: This study is part of a longitudinal cohort undertaken in both women and men to describe live birth outcome after undergoing assisted reproductive technology (ART) treatment in a clinical setting. Another objective was to follow women and men living with children from other alternatives after ART, such as adoption. Material and methods: A total of 439 (80.5%) women and 423 (77.6%) men were included in the baseline cohort (2005–2007). Live birth rate after ART was 24.8% at baseline. Up to 5 years later (2010–2011) the same participants were sent individual postal questionnaires ( n = 439). Results: Overall, 278 (63.3%) women and 183 (41.7%) men filled in and returned the questionnaire at follow up. The majority of women (91.7%) and men (93.4%) were living with children. A total of 225 (80.9%) women had a live birth at follow up. Of these, almost three of four (71.6%) had a live birth after ART and more than one of four (28.0%) after spontaneous pregnancies or both. Of these, 52 (26.1%) women had a subsequent live birth after successful ART and 26 (32.9%) women after unsuccessful ART. Nineteen (6.8%) women and 13 (7.1%) men had a child after adoption. Almost one of five (19.1%) women had no live birth at follow up. Conclusion: The majority of women and men were living with children, resulting from a live birth after ART, spontaneous pregnancy and/or adoption up to 5 years later. However, almost one of five had no live birth at follow up.